1998
DOI: 10.2214/ajr.170.6.9609160
|View full text |Cite
|
Sign up to set email alerts
|

Neoplastic pancreaticobiliary duct obstruction: evaluation with breath-hold MR cholangiopancreatography.

Abstract: The purpose of this study was to investigate the use of breath-hold single-shot fast spin-echo MR cholangiopancreatography in neoplastic pancreaticobiliary duct obstruction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
45
1

Year Published

1999
1999
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(49 citation statements)
references
References 7 publications
3
45
1
Order By: Relevance
“…Some ampullary carcinomas are covered by intact epithelium, and the accuracy of biopsies is reportedly lower in the tumors with intra-ampullary growth compared with tumors with extraampullary growth or ulceration. 10,14,15 We found that the preoperative diagnosis of moderate or severe dysplasia on biopsy should be viewed as suspicion for carcinoma. EST had some limitations, including the interference with EUS staging and histologic examination due to tissue destruction, and possible complications such as hemorrhage, perforation, or pancreatitis.…”
Section: Discussionmentioning
confidence: 97%
“…Some ampullary carcinomas are covered by intact epithelium, and the accuracy of biopsies is reportedly lower in the tumors with intra-ampullary growth compared with tumors with extraampullary growth or ulceration. 10,14,15 We found that the preoperative diagnosis of moderate or severe dysplasia on biopsy should be viewed as suspicion for carcinoma. EST had some limitations, including the interference with EUS staging and histologic examination due to tissue destruction, and possible complications such as hemorrhage, perforation, or pancreatitis.…”
Section: Discussionmentioning
confidence: 97%
“…Multiple studies have demonstrated the utility of MRCP in evaluating patients with CC [106,107] . MRCP has diagnostic accuracy comparable to invasive cholangiographic techniques such as ERCP or percutaneous transhepatic cholangiography (PTC) [108][109][110][111] .…”
Section: Magnetic Resonance Imaging (Mri) and Magnetic Resonance Cholmentioning
confidence: 99%
“…On MRCP, ECC may appear as extrahepatic lesions with similar signal intensity of ICC on both T1-and T2-weighted images, in addition to proximal biliary dilatation [106,116] . A meta-analysis of 67 studies (4711 patients) evaluating MRCP performance in patients with suspected biliary diseases showed an overall sensitivity of 88% and specificity of 95% [107] . In a series of 99 patients with HCC, MRCP accurately determined the longitudinal extension of the tumor in 88% of patients [118] .…”
Section: Magnetic Resonance Imaging (Mri) and Magnetic Resonance Cholmentioning
confidence: 99%
“…3D-MRCP has a higher resolution (1 mm 3 ), excellent image quality, and was superior to ERCP/PTC in assessing hilar ductal obstruction. Indeed, several previous studies demonstrated that the accuracy of 2D-MRCP in assessing the level and feature of bile duct obstruction was comparable to that of ERCP/PTC (1,6,12,17,(22)(23)(24)(25)(26). However, at the same time, in several studies where surgical and pathological findings were used as a standard of reference, 2D-MRCP showed a relatively low accuracy regarding tumoral extent of the biliary tree (25)(26)(27).…”
Section: D Mrcp In Malignant Obstructionmentioning
confidence: 99%
“…MALIGNANT BILIARY OBSTRUCTION is one of the most challenging problems encountered by clinicians today in regard to differential diagnoses and management planning (1). Traditionally, for the direct visualization of the ductal system, invasive methods such as endoscopic retrograde cholangiopancreatography (ERCP) and percutaneous transhepatic cholangiography (PTC) have been used.…”
mentioning
confidence: 99%